The Influence of the Roles of School Supervisors, Principals, and School Committees on the Quality of Public Elementary Schools in Rembang District Rembang Regency - Dianti, Wahyuni Rahma; Egar, Ngasbun; Abdullah, Ghufron (Journal of Educational Sciences, 2025)
The quality of public elementary schools in Rembang District, Rembang Regency, varies considerably, with some schools achieving high performance while others continue to face challenges in literacy, numeracy, and character development. This situation underscores the importance of examining the contributions of school supervisors, principals, and school committees to school quality. This study aims to analyze the influence of these three roles on the quality of public elementary schools. A quantitative approach with a survey method was used, involving 188 teachers from 42 schools selected through proportional random sampling. Data were collected using a validated and reliable questionnaire and analyzed with simple and multiple regression techniques. Results show that, partially, the roles of school supervisors and principals significantly influence school quality (p = 0.001 and p = 0.004), but with negative regression coefficients, while the school committee’s role is not significant (p = 0.800). Simultaneously, the three roles significantly affect school quality (p = 0.000) with an R² of 8.8%. Strengthening leadership, supervision, and committee involvement is essential for sustainable improvement.